UMPSAs Ziarah Prihatin to assess needs of prospective students - Naqiah, Puaad (UMPSA, 2024)
KELANTAN, 20 September 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is welcoming new students in need as part of an initiative to facilitate their registration on 28 September.